2023
DOI: 10.3390/su15021493
|View full text |Cite
|
Sign up to set email alerts
|

Halal Healthcare Services: Patients’ Satisfaction and Word of Mouth Lesson from Islamic-Friendly Hospitals

Abstract: This study aims to investigate the impact of halal healthcare attributes, intrinsic value, and extrinsic value on satisfaction, and explores how patient satisfaction with halal healthcare services influences word of mouth (WOM) to others. The cross-sectional survey was conducted in two cities with four Islamic-friendly hospitals across Malaysia. This study used purposive and non-probability random sampling methods. Partial least square (PLS) technique was used for data analysis of 309 Muslim patients with a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
0
7
0
2
Order By: Relevance
“…Parasuraman (2005) forms a "gap measure" to compare how customers perceive a service with how they anticipate its performance, either by pleasure or disappointment (Parasuraman et al, 2005). In the aspect of halal health, the desire of patients to have health facilities based on halal principles can affect their satisfaction with healthcare providers' provision of health facilities (Medhekar & Haq, 2018;Naserirad et al, 2022;Rahman et al, 2023;Widiasih et al, 2020). Aladwan (2021) and Nugraha (2020) imply loyalty and WOM valuation of healthcare products and services regarding significance/insignificance and benefits/disadvantages (Aladwan et al, 2021;Nugraha, 2020).…”
Section: Underpinning Theorymentioning
confidence: 99%
See 4 more Smart Citations
“…Parasuraman (2005) forms a "gap measure" to compare how customers perceive a service with how they anticipate its performance, either by pleasure or disappointment (Parasuraman et al, 2005). In the aspect of halal health, the desire of patients to have health facilities based on halal principles can affect their satisfaction with healthcare providers' provision of health facilities (Medhekar & Haq, 2018;Naserirad et al, 2022;Rahman et al, 2023;Widiasih et al, 2020). Aladwan (2021) and Nugraha (2020) imply loyalty and WOM valuation of healthcare products and services regarding significance/insignificance and benefits/disadvantages (Aladwan et al, 2021;Nugraha, 2020).…”
Section: Underpinning Theorymentioning
confidence: 99%
“…Some previous studies identified halal facilities for healthcare, including sharia facilities, doctor's facilities, nursing services, medical expertise, medical facility atmosphere, and administrative conduct (Medhekar & Haq, 2018;Naserirad et al, 2022;Ningtyas et al, 2022;Padela et al, 2012;Rahman et al, 2023).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations